Colibacillosis in poultry: A review - Panth, Yuvraj (Journal of Agriculture and Natural Resources, 2019)
Avian colibacillosis is caused by a group of pathogens designated avian pathogenic Escherichia coli (APEC). Despite being known for over a century, avian colibacillosis remains one of the major endemic diseases afflicting the poultry industry worldwide. Autologous bacterins provide limited serotype-specific protection, yet multiple serogroups are associated with disease, especially O1, O2 and O78 among many others. This article provides the vital information on the epidemiology, diagnosis, control and treatment strategy for avian colibacillosis. A better understanding of the information addressed in this review article will assist the poultry researchers and the poultry industry in continuing to make progress in reducing and eliminating avian colibacillosis from the poultry flocks.